“Biomechanical Signaling in Oocytes and Parthenogenetic Cells” - Pennarossa, Georgia; Gandolfi, Fulvio; Brevini, Tiziana A. L. (Frontiers in Cell and Developmental Biology, 2021)
Oocyte-specific competence remains one of the major targets of current research in the field of reproduction. Several mechanisms are involved in meiotic maturation and the molecular signature of an oocyte is considered to reflect its quality and to predict its subsequent developmental and functional capabilities. In the present minireview, we focus on the possible role of mechanotransduction and mechanosensor signaling pathways, namely the Hippo and the RhoGTPase, in the maturing oocyte. Due to the limited access to female gametes, we propose the use of cells isolated from parthenogenetic embryos as a promising model to characterize and dissect the oocyte distinctive molecular signature, given their exclusive maternal origin. The brief overview here reported suggests a role of the mechanosensing related pathways in oocyte quality and developmental competence and supports the use of uniparental cells as a useful tool for oocyte molecular signature characterization.